Safety and Efficacy of Transurethral Cystolithotripsy in Pediatric Population: A Single Center Study - Tariq Ahmad, Sohail Shabbir, Mushtaq Ahmad, Muhammad Asif Ammar (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Bladder stone treatment in children is evolving rapidly. Vesicolithotomy has now been rarely used except in very large stone and even larger stones are treated with percutaneous cystolithotripsy, which is still more invasive compared with transurethral cystolithotripsy. We have evaluated a series of 150 case of bladder stone in children with this minimal approach through natural orifice i.e. urethra to assess its feasibility, efficacy and complications. Objective: To assess the safety and efficacy of transurethral cystolithotripsy for bladder stone in pediatric population. Material and Methods: This study was conducted in the Institute of Kidney Diseases and Transplant HMC Peshawar Pakistan from Jan 2020 to Apr 2022. A series of 150 patients were assessed with a mean age of 7.5+-2.9 years and mean stone size of 11.2+-3.6mm. Mean operative time was 28.1+- 5.8 minutes, mean hospital stay was 0.2+-1. A total of 89.33% of were treated as a day case. Two patients (1.3%) needed re-cystolithotripsy while in none of the cases were converted to open or PCCL. Postoperatively 16 (10.67%) patients developed Clavien grade 1 complications and 2(1.33%) patients developed Clavien grade III complication. Conclusion: Trans-urethral cystolithotripsy is feasible and effective in pediatric population with acceptable clearance rate and low grade complication for stones up to 20 mm. However comparison with open method is needed. Keywords: Bladder stone, Trans-urethral, Cystolithotripsy.